Centrifuge modelling of energy piles subjected to heating and cooling cycles in clay. Issue 4 (29th September 2014) - Gunawan, A.; Ng, C. W. W.; Laloui, L.; Shi, C.
Abstract : Energy pile foundations can discharge heat into the ground in summer and extract heat from the ground in winter. The cyclic temperature change in piles may induce serviceability problems. At present, the effects of cyclic heating and cooling on the displacement patterns of energy piles are not fully understood. This letter describes a new heating and cooling system developed to control the cyclic temperature in energy piles in a centrifuge. The system is able to control the temperature in an energy pile between 3 and 90°C. Using this system, two tests were carried out to investigate the effects of cyclic heating and cooling between 9 and 38°C on the long-term displacement of an energy pile in lightly overconsolidated (overconsolidation ratio (OCR)  =  1ṡ7) and heavily overconsolidated (OCR  =  4ṡ7) kaolin clay. Under a constant working load, a ratcheting displacement mechanism was observed for both energy piles over five cycles of heating and cooling. The pile in the lightly overconsolidated clay settled continuously but at a reduced rate and the settlement eventually reached 3ṡ8% D (pile diameter). This may be due to a stress reduction caused by plastic contraction of the clay and thermally accelerated creep at the pile–soil interface. In comparison, a relatively smaller settlement of 2ṡ1% D was observed for the pile in heavily overconsolidated clay.